Simulium (Simulium) lomkaoense, a new species of black fly (Diptera: Simuliidae) from Thailand - Takaoka,H. (Entomological Society of America, 2015)
© 2014 Entomological Society of America. Simulium (Simulium) lomkaoense sp. nov. is described from females, males, pupae, and larvae in Thailand. This new species is assigned to the Simulium malyschevi Dorogostaisky, Rubtsov & Vlasenko species-group of the subgenus Simulium, and appears to be closely related to Simulium baimaii Kuvangkadilok & Takaoka from Thailand in having a similar shape of the female and male genitalia, pupal gill with two inflated filaments, and simple wall-pocket-shaped cocoon. This new species is compared taxonomically with S. baimaii and other related species. It represents the third species of the S. malyschevi species-group known from Thailand.